The exposure assessment of thermal exposure and safety and health inspection of a selected warehouse in Klang Valley / Chan Hui Xuan - Chan , Hui Xuan (2017)
Health and safety are important features in the workplace, as we spend a large amount of time at different types of workplaces. In retail and warehousing services especially, storage of products poses a hazardous risk if not managed properly. Air movement, temperatures, stock positioning, general cleanliness and lighting contributes to the overall safety of workers working in these warehouses. This thesis serves to contribute to the discussion on improving the quality of warehouse management through effective environmental health and safety. The focus is in identifying the relationship between the outdoor and indoor temperatures in a warehouse to the level of comfort experienced by the personnel in charge of managing the warehouse, leading to the productivity level of the supervisor. As for goods stored in the warehouse, impact of work place hazards on the safety of staff entering the warehouse is analyzed. The current company SOP is evaluated if gaps exist in implementation. Readings of thermometer placed in warehouse are analyzed. The research showed that the positioning of the existing stocks in the warehouse constitutes an obstruction to the emergency exits. These obstructions also restricted the air flow circulation, making it quite unventilated to work for a longer period of time. Records showed that temperatures were on the high side, with some months exceeding 30oC. It is recommended that the temperature range be reset to a narrower range as the optimum temperature for thermal comfort is between 18 to 26oC, as well as for electricity savings. In conclusion, the temperature range can be reduced to between 15oC to 25oC by taking into account the optimal thermal comfort and the impact of relative humidity in the warehouse on the products stored. Various trainings on warehouse safety should be adapted to different levels of workers working in the warehouse or those who need to use the warehouse. Additional storage place or special section should be allocated to cater for extra stocks arrived during peak seasons.